Model Pembelajaran Pendidikan Agama Islam Inklusi Sekolah Dasar Negeri di DKI Jakarta - Kristo Paulus; Erlina Erlina (Universitas Indraprasta PGRI Jakarta, 2023)
Learning models for Inclusive Islamic Religious Education at SDN Pisangan Baru 01 and SDN Klender 03 Pagi Jakarta need to be made. The learning model can be implemented for slow learners, taking into account the following matters: preparing teaching materials to meet the unique and specific needs of students, the most effective learning methods to be used in delivering learning materials, providing encouragement continuously. To let the students know that we pay attention to them in the class, eye contact during learning process is very important, give credit for their presence. parental support, encouragement and assistance are closely related to slow students’ learning outcomes. In qualitative research, the instrument or research tool is the researcher himself. The approach used in this study is to use a phenomenological approach. This study aims to examine the learning conditions of inclusive Islamic religious education in public elementary schools, as well as to analyse, evaluate and model the learning of inclusive Islamic religious education in public elementary schools.